2004
DOI: 10.1007/s00418-003-0599-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatidylinositol-dependent bond between alkaline phosphatase and collagen fibers in the periodontal ligament of rat molars

Abstract: Alkaline phosphatase (ALP) is anchored to the outer leaflet of the lipid bilayer via phosphatidylinositol (PI) and ALP activity has been localized in the plasma membrane of numerous tissues. In the periodontal ligament ALP activity is found in the collagen fibers in addition to the plasma membrane of the osteoblasts and fibroblasts. In this study, we examined the distribution of ALP activity in the periodontal ligament of rat molars and also examined whether the bond between ALP and collagen fibers is dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…This might be due to the activation of MAP kinase by CXCL12 [52], [53], which induces up-regulation of COL1A1 [54][56] and ALP [57], [58]. In addition, COL1A1 and ALP are requisite factors of PDL fibroblasts [59]. Collagen type I is a primary component of periodontal fibers and ALP is located in collagen fibers and fibrils, which are different characters from other connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This might be due to the activation of MAP kinase by CXCL12 [52], [53], which induces up-regulation of COL1A1 [54][56] and ALP [57], [58]. In addition, COL1A1 and ALP are requisite factors of PDL fibroblasts [59]. Collagen type I is a primary component of periodontal fibers and ALP is located in collagen fibers and fibrils, which are different characters from other connective tissues.…”
Section: Discussionmentioning
confidence: 99%
“…An important physiological function of ALP is to catalyze the bone generation and mineralization. ALP activity increases during the development of bone formation (Coleman ; Nakamura, Noda, Shimpo, Oikawa, Kawasaki & Hirashita ). In this study, the plasma ALP activity of the soft‐shelled turtles showed the exact patterns as the plasma ALP activity reported in tilapia (Lin et al .…”
Section: Discussionmentioning
confidence: 99%
“…Critical for successful immunolocalization was the use of acetic acid for demineralization of the methanol-fixed tissue. A throughout controlled study in regard to fixation and incubation conditions revealed alkaline phosphatase not only at membranes of osteoblasts and fibroblasts of the periodontal ligament but additionally on collagen fibers of the extracellular matrix (Nakamura et al 2004).…”
Section: New Methods and Toolsmentioning
confidence: 99%